QR-Code Assisted PAI E-Module Design: A Development Study to Improve Learning Outcomes - Nova Rahmadayanti; Adelia Lestarina; Nachua Qinanthi; Dea Asmara; Azra Tajhizi (WISE Pendidikan Indonesia, 2026)
This study focuses on the development of a QR Code-based electronic teaching module for Islamic Religious Education (PAI) aimed at improving the learning outcomes of grade VII students at SMP Negeri 16 Bandar Lampung. In line with the importance of utilizing digital learning tools within the context of the Merdeka Curriculum, this research addresses the challenges of traditional Islamic education by integrating multimedia elements and interactivity through the use of QR Codes. The QR Code in the e-module connects students to additional digital content such as videos, interactive exercises, and enrichment readings, facilitating a more engaging and flexible learning experience. This study uses a Research and Development (R&D) approach with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The results from the development phase show very high feasibility, with expert validation scores of 97% for content, 95% for language, and 74% for media design, all categorized as highly feasible for educational use. Additionally, the implementation phase showed positive student engagement, with a significant improvement in learning outcomes, as evidenced by an N-Gain score of 0.69 and Paired Samples T-Test results showing significant improvement (p<0.001). This study contributes to the development of digital learning tools by highlighting the potential of QR Code-based modules to support independent learning and enhance understanding of Islamic teachings. The study also emphasizes the importance of context-appropriate design in the integration of digital tools in Islamic education.